Prevention of tetracycline hepatotoxicity by nicardipine - Felek, S.; Kilic, S.S.; Ozercan, M.R.; Ocak, S.; Yekeler, H.; Akbulut, A.; Ilhan, N. (My University, 1994)
This investigation was performed to determine the effects of nicardipine, a calcium channel blocker, on tetracycline hepatotoxicity. Forty-five male, Balb/c mice were separated into three groups. In the first two groups, 2 g/l tetracycline or 2 g/l tetracycline plus 300 mg/l nicardipine was added to the drinking water. The last group of mice received only tap water. The mice were given the drugs for 15 days. After 15 days the mice were killed, liver and blood samples were collected, and aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase were measured in the sera. Histopathological evaluation was carried out. In the tetracycline group, AST, ALT, and alkaline phosphatase levels were found to be 352.9 ± 70.3 U/l, 97.7 ± 25.5 U/l, and 135.1 ± 89.6 U/l; in tae tetracycline plus nicardipine group, 251.1 ± 61.7 U/l, 79.0 ± 25.2 U/l, and 57.9 ± 37.6 U/l; and in the control group, 247.7 ± 63.5 U/l, 81.3 ± 23.0 U/l, and 38.1 ± 33.3 U/l, respectively. All biochemical parameters in the tetracycline plus nicardipine group were found to decrease significantly (p < 0.01). In the tetracycline plus nicardipine group, mononuclear cell infiltration and fibrosis in portal tracts, disarrangement of hepatocytes, focal necrosis, and activation of Kupffer cells in lobules were all found to be significantly decreased (p < 0.05). In conclusion, nicardipine may be a potentially useful agent for the prevention of tetracycline hepatotoxicity.
Keywords: antibiotic; calcium channel blockers; hepatotoxicity; nicardipine; tetracycline